Pengaruh Faktor Makroekonomi dan Faktor Fundamental Terhadap Return Saham Perusahaan yang Listing di Jakarta Islamic Index Periode 2012-2016) - Hanifa Nurhidayati; Ari Prasetyo (Universitas Airlangga, 2019)
The goal of this research is to determine the effect of corporate Macroeconomics Factor and Fundamental Factor on Stock Return of Listed Companies in Jakarta Islamic Index (JII) partially or simultaneously. The method of research used is the quantitative approach. The sample of the research is are 20 companies registered in Jakarta Islamic Index that meet the criteria of purposive sampling. The analysis technique used best estimation model by Common Effect Model (CEM) and the result is Y = 3,190398 + 0,0013Inflasiit + 0,0001BiRateit + 0,0341GDPit - 0,1246EPSit + 0,000DERt+ 0,1744CRt and R2 24,24%. The result of the partial test shows that Inflation and Return On Equity ratio has a significant effect. The result of the simultaneous test shows that the four variables have significant effects in company stock return registered in Jakarta Islamic Index.Keywords: Return Stock, Current Ratio, Return On Equity, Earning Per Share, Debt to Equity Ratio, GDP, Bi Rate, Inflation,Jakarta Islamic IndexREFERENCES Agnes, Sawir, 2009. Analisa Kinerja dan Perencanaan Keuangan Perusahaan, Jakarta; PT. Gramedia Pustaka Utama.Anatasia, Njo dan Imelda wijayanti. 2003. Analisis Faktor Fundamental Dan Risiko Sistematik.Ang, Robert .1997. Pasar Modal Indonesia : Media Soft Indonesia.Brigham, Eugene F. dan Gapenski, Louis C. 1997. Financial Management Theory and Practice. Orlando : The Dryden Press.Boediono. 2009. Teori Pertumbuhan Ekonomi. Yogyakarta : BPFE UGM.Gumandi, T. A. 2011. Manajemen Investasi. Jakarta: Mitra Wacana Media.Hery, S.E., M.Si, “Analisis Laporan Keuangan”, (Center for Academic Publishing Service; Yogyakarta, thn 2015), hlm 29.Herlambang, T. 2001. Ekonomi Makro: Teori, Analisa, dan Kebijakan. Jakarta: Gramedia Pustaka Utama.Hartono, Jogiyanto, 1998, Teori Portofolio dan Analisis Investasi. Edisi pertama. BPFE. Yogyakarta.A Helfert, Erich. 2002. Teknik Analisis Keunagan. Jakarta, Penerbit Airlangga.Liauw, Joven Sugianto. 2013. Analisis Pengaruh Inflasi, SBI, Nilai Tukar terhadap Indeks Saham Gabungan. Jurnal Ilmiah. STIE MDP, 2013. Mankiw, N.Gregory, 2007. Makroekonomi. Edisi keenam. Jakarta: Erlangga.Samsul, Mohammad. 2006. Pasar Modal dan Manajemen Portofolio. Surabaya: Erlangga.Suhartono dan Qudsi, Fadillah, 2009. “Portofolio Investasi dan Bursa Efek Pendekatan Teori dan Praktik”,Yogyakarta, UPP STIM YKPN.Susilo D, Bambang, 2009. “Pasar Modal”. Yogyakarta: UPP STIM YKPN Yogyakarta.Tandelilin, Eduardus. 2010. Portofolio dan Investasi: Teori dan Aplikasi. Edisi Pertama. Yogyakarta: KANISIUS.